Analysis and assessment of Kazakhstan’s social infrastructure development - Spanova , B.K. (BUKETOV BUSINESS REVIEW, 2017)
The current stage in social policy development in the Republic of Kazakhstan is characterized by significant changes in defining approaches to the social policy. It is caused by changing society’s social structure, new relations’ emergence in this regard and changing its nature according to the worldwide trend in sociallyoriented market economy development. The article is devoted to studying the state of provision with infrastructural objects in the Republic of Kazakhstan. Social infrastructure development tendency has been revealed, main directions of the social infrastructure development have been determined.The main ways of the region’s social infrastructure effective development are shown. The author emphasized some important factors that have a significant impact on a sustainable development of social infrastructure facilities’ functioning. Social infrastructure development is not only an urgent problem, but also a problem of a long-term nature that determines the need to implement reforms in the social sphere in the context of economic relations’ transformation. In this regard, the solution of the problems in social infrastructure development largely determines its successful development, both at this point of time and in the future.